Sweden : Financial Sector Assessment Program-Technical Note-Supervision and Oversight of Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Sweden in the areas of supervision and oversight of financial market infrastructures (FMIs). FMIs in Sweden are subject to appropriate and effective supervision and oversight by the Finansinspektionen (Financial Supervisory Authority, FI) and Sveriges Riksbank (Riksbank). The scope, basis, and objectives of each authority's supervision and oversight are clearly defined and disclosed. There is evidence that the authorities' supervision and oversight have effectively improved risk management practices at Swedish FMIs. There is also effective cooperation between the FI and Riksbank in the supervision and oversight of FMIs. The risk management at Nasdaq Clearing appears to be sound.